Taqwīm Muta‘allimī al-Lughah al-‘Arabīyah li-Ghayr al-Nāṭiqīna bi-hā fī Ḍaw’ al-Kifāyāt al-Maṭlūbah Minhum - Maimun Bin Ahmad Alsolamy (Al-Ma‘rifah, 2018)
The evaluation of Arabic language learners to non-native speakers is linked to the competencies required to enable them, and to the goals or competencies specified in advance. Valuation is based on it to see the extent of its realization or not. The study aimed to know the competencies required to enable Arabic language learners to non-native speakers of it, and to methods of evaluating Arabic language learners to non-native speakers in light of it, and the study used the descriptive approach. The study concluded: the goal of teaching Arabic to non-native speakers is to empower learners with linguistic, communication, and cultural competencies, and that evaluating Arabic language learners to non-native speakers is according to the three competencies, and those linguistic activities have a role in evaluation, in developing and developing competencies, and that all kinds of language tests It is part of the evaluation of learners of the Arabic language for non-native speakers and is not the only method of evaluation.